Dr. Falak Khanna, Assistant Professor, Department of Commerce, Gurugram University, Gurugram. (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Training and development programs play a vital role in enhancing the performance and productivity of employees within an organization. This research paper aims to explore the impact of training and development on employee performance and productivity. The study will examine the importance of training and development programs in improving employee skills, knowledge, and competencies. It will also investigate how training and development initiatives can lead to increased employee motivation, engagement, and job satisfaction. Additionally, the research will analyze the impact of training and development on organizational performance and effectiveness.The study will utilize a combination of qualitative and quantitative research methods to gather data from employees and managers within various organizations. Surveys, interviews, and case studies will be conducted to collect information on the training and development practices, employee performance, and productivity levels. Statistical analyses will be used to evaluate the relationship between training and development and employee performance. The findings of the research will provide valuable insights into the role of training and development in enhancing employee performance and productivity.